Experimental Study of lncRNA RP11-815M8.1 Promoting Osteogenic Differentiation of Human Bone Marrow Mesenchymal Stem Cells. (27th March 2021) - Sun, Xiang; Cao, Junchuan; Han, Jiusong; Jia, Bo; Wang, Jing; Lian, Junxiang; Gao, Jianwei; Liu, Shuguang; Xiao, Hui
Abstract : Objective . This study is aimed at investigating the role of long noncoding RNA (lncRNA) RP11-815M8.1 in the osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs). Methods . RT-PCR was used to detect the expression of lncRNA RP11-815M8.1 before and after osteogenic differentiation of hBMSCs. The lncRNA RP11-815M8.1 in hBMSCs was overexpressed or silenced via lentiviral transfection. The transfection efficiency was detected by RT-PCR, and the proliferation of hBMSCs was determined by CCK-8. After 14 days of osteogenic differentiation of transfected hBMSCs, the expression of osteogenic transcription factors (ALP, OCN, OPN, Runx2, and Osterix) was detected by alizarin red staining and RT-PCR. The mRNAs directly regulated by lncRNA RP11-815M8.1 and targeted miRNAs were analyzed according to the positional relationship between lncRNA and mRNA in the genome and miRanda software. Results . The expression of lncRNA RP11-815M8.1 enhanced with increasing osteogenic differentiation time of hBMSCs. Two days after the transfection of hBMSCs, lncRNA RP11-815M8.1 expression was significantly increased in the overexpression group and significantly decreased in the knockdown group, compared to control cells. The CCK-8 assay showed that overexpression and knockdown of lncRNA RP11-815M8.1 did not affect the proliferation of hBMSCs. After 14 days of differentiation of hBMSCs, stronger alizarin red staining was observed in the overexpression groups, and the expression of osteogenic transcription factors was increased in the overexpression group compared to the control. In the knockdown group, alizarin red staining and the expression of osteogenic transcription factors were decreased. Bioinformatics analysis showed that lncRNA RP11-815M8.1 was directly associated with one mRNA, 27 interacting miRNAs, and 20 miRNA-targeted mRNAs. Conclusion . The osteogenic differentiation of hBMSCs can be promoted by lncRNA RP11-815M8.1 in vitro.